(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Introduction Targon locking plate (TLP) of femoral neck with cannulated screws was used in management of fracture neck femur in young adults. The aim of this study is to compare the clinical, functional and radiological results of using Targon locking plate versus cannulated cancellous screws (CCS) in management of femoral neck fracture. Patients and methods This was a prospective randomized controlled study conducted in Beni-Suef University Hospital in the period from November 2019 to October 2021. The study includes 50 patients presented with intracapsular fracture neck femur. They were divided into two groups; the first group for patients treated with Targon locking plate (TLP) and the second group for Cannulated cancellous screw (CCS) system. Results There was a statistically significant increase in operative time in Targon TLP group. Postoperative mean VAS score was significantly lower in TLP (3.086) than in CCS group (4.5) and also the mean HHS showed statistically significant improvement in TLP group (83.4 ± 2.1) as compared with CCS group (72.1 ± 3.2) (P < 0.05). Also, femoral neck shortening and nonunion rates were higher in CCS group. Conclusion TLP for femoral neck fractures improves hip functional recovery and reduces the femoral neck shortening and nonunion rate. Thus, TLP can be an alternative to CCS for the treatment of femoral neck fractures.